2016
DOI: 10.1097/pec.0000000000000868
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chest Radiography on Antibiotic Treatment for Children With Suspected Pneumonia

Abstract: Among children with high suspicion for pneumonia, CXRs infrequently altered the initial plan for antibiotics. However, when clinical suspicion for pneumonia was low, the use of CXR may reduce unnecessary antibiotic use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 20 publications
4
32
0
1
Order By: Relevance
“…Introduction of a clinical pathway for young febrile infants showed reduced time to first antibiotic dose, but did not evaluate the effect on antibiotic prescription itself ( 53 ). The use of chest radiographs in particular reduces antibiotics in children with low clinical suspicion of pneumonia ( 54 ). For all other interventions no significant reduction was found on antibiotic prescription ( 46 , 49 , 65 , 69 , 70 ).…”
Section: Resultsmentioning
confidence: 99%
“…Introduction of a clinical pathway for young febrile infants showed reduced time to first antibiotic dose, but did not evaluate the effect on antibiotic prescription itself ( 53 ). The use of chest radiographs in particular reduces antibiotics in children with low clinical suspicion of pneumonia ( 54 ). For all other interventions no significant reduction was found on antibiotic prescription ( 46 , 49 , 65 , 69 , 70 ).…”
Section: Resultsmentioning
confidence: 99%
“…31 Previous studies have reported that antibiotic prescribing is not statistically impacted by the radiologist's impression from the CXR. 21,32 Therefore, ED CXR results were not included in determining the propensity score. A 1:1 nearestneighbor matching without replacement based on propensity score was executed by using the MatchIt package in the R statistical program.…”
Section: Figurementioning
confidence: 99%
“…9 Authors of another study found that ED providers who had a high suspicion of pneumonia for their patients had a sixfold increased odds of prescribing antibiotics regardless of CXR results, revealing that CXR findings do not typically alter a provider's decision to prescribe antibiotics. 30 No statistical differences in antibiotic prescribing between the preintervention and intervention periods was detected, although there was a 4.7% decrease in the ordering of CXRs during the study period. We support the recommendation that CXRs are not routinely required for the diagnoses of CAP in the PPCP.…”
Section: Figurementioning
confidence: 78%